To study attitude towards credit card, BNPL, and personal loans among people living in Ahmedabad city. - Harshil Madhvani; Jignesh Vidani (Journal of Advanced Research in Entrepreneurship, Innovation and SMES Management, 2026)
In recent years, the growth of digital finance and consumer credit tools such as credit cards, Buy Now Pay Later (BNPL) services, and personal loans has transformed individual borrowing behaviour in urban India. This study investigates the attitudes of individuals living in Ahmedabad city toward these credit instruments, with a particular focus on the influence of age as a demographic factor. A structured questionnaire was administered to 240 respondents across different age groups, and the data were analysed using the chi-square test of independence to explore associations between age and various attitudinal statements. The results revealed that all 30 hypotheses tested showed statistically significant relationships between age and credit-related attitudes (p < 0.05). However, the strength of the association in all cases was weak, as indicated by low correlation values (Cramér’s V). This suggests that while age plays a role in shaping credit attitudes, other factors such as income, education, financial literacy, and digital access may have a stronger influence. The study contributes to behavioural finance literature by demonstrating the changing perceptions of credit usage in a digitally evolving economy. It also highlights the need for targeted financial education and responsible lending practices. Financial institutions, fintech platforms, and policymakers can leverage these insights to develop more consumer-centric credit products and awareness programmes that address behavioural patterns beyond age.